Acute renal artery thrombosis treated with combination use of multiple interventional techniques - Zhang, Naiding; Xiong, Guiya; Pan, Yifeng; Shao, Changming; Wang, Jian; Chen, Bing; Liu, Zhenjie (Journal of Cardiovascular Medicine and Cardiology, 2019)
Purpose: To describe the combined use of multiple interventional techniques for the treatment of acute renal artery thrombosis. Case Report: Acute renal artery thrombosis is a rare condition, which is difficult to diagnose accurately and quickly. Failure to restore renal perfusion as quickly as possible may lead to renal dysfunction. Multiple interventional techniques are used as new options to restore renal blood flow and function. Herein we present one case of acute renal artery thrombosis treated with combination use of percutaneous rheolytic thrombectomy, catheter thrombus aspiration and intra-arterial thrombolysis in a very early stage. Conclusion: Early diagnosis and treatment are essential to preserving the renal function, and the combined use of multiple interventional techniques is safe and effective for the restoration of renal perfusion in treating patients with acute renal artery thrombosis.